2003
DOI: 10.1074/jbc.m302714200
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Motif of the Drosophila Morphogenetic Protein Bicoid Critical to Transcription Control

Abstract: Bicoid is a molecular morphogen-controlling embryonic patterning in Drosophila. It is a homeodomain-containing protein that activates specific target genes during early embryogenesis. Our recent studies have identified a domain of Bcd located outside its homeodomain and referred to as a self-inhibitory domain that can dramatically repress its own ability to activate transcription. Here we present evidence that the self-inhibitory function is evolutionarily conserved. A systematic analysis of this domain reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Our experiments show that overexpression of dCBP can partially restore the activity of Bcd(A52-56) on the hb-CAT reporter in S2 cells. 2 This derivative is normally inactive on this reporter due to a strengthened self-inhibitory func- tion (20,27). These findings further highlight the importance of a well controlled balance between HAT and HDAC activities in regulating transcription.…”
Section: Fig 2 Bcd and Dcbp Interact With Each Othermentioning
confidence: 68%
See 3 more Smart Citations
“…Our experiments show that overexpression of dCBP can partially restore the activity of Bcd(A52-56) on the hb-CAT reporter in S2 cells. 2 This derivative is normally inactive on this reporter due to a strengthened self-inhibitory func- tion (20,27). These findings further highlight the importance of a well controlled balance between HAT and HDAC activities in regulating transcription.…”
Section: Fig 2 Bcd and Dcbp Interact With Each Othermentioning
confidence: 68%
“…Our previous experiments have shown that increasing the spacing between the symmetric pairs of Bcd binding sites can alter the Bcd protein domains required for cooperative DNA binding and the sensitivity to a self-inhibitory function of the protein (20). These experiments suggested that enhancer architecture can influence how Bcd utilizes its domains for different functions (20,41).…”
Section: Fig 2 Bcd and Dcbp Interact With Each Othermentioning
confidence: 99%
See 2 more Smart Citations
“…SAP18 was purified as part of a mammalian SIN3 complex (28). It has also been shown to interact with Drosophila bicoid, which interacts with the PAH3 and -4 domains of SIN3 (37,52). Based on these results, Singh et al (37) hypothesized that SAP18 would be a component of the Drosophila SIN3 complex.…”
Section: Sin3 Isoforms Interact With a Common Set Of Proteins-mentioning
confidence: 99%